DINAMIKA SPASIO-TEMPORAL KEMISKINAN DI PULAU JAWA 2020-2023 - Ni Luh Putu Ari Susiawati; Novelia, Friska; Wahyu Oktaviana, Siska; Zacky Arie Pratama, Muhammad (Polytechnic of State Finance STAN, 2025)
The inability of individuals or households to adequately meet their basic needs remains an important issue in Indonesia's development, especially on Java Island, which is the economic hub but has the highest number of poor people. This study aims to analyze the spatial and temporal dynamics of poverty levels on Java Island during the period 2020–2023 using the Geographically and Temporally Weighted Regression (GTWR) approach. The variables analyzed include RLS, GRDP, TPT, UMK, and Population Density. The results show that the GTWR model with an adaptive exponential kernel performs best (R² = 79.51%) compared to OLS (R² = 61.4%). Average Years of Schooling (RLS) is the most dominant factor in reducing poverty, both individually and in combination with GRDP. Ketidakmampuan individu atau rumah tangga dalam memenuhi kebutuhan dasar secara layak masih menjadi isu penting dalam pembangunan di Indonesia, termasuk di Pulau Jawa yang merupakan pusat ekonomi namun memiliki jumlah penduduk miskin tertinggi. Penelitian ini bertujuan untuk menganalisis dinamika spasial dan temporal tingkat kemiskinan di Pulau Jawa selama periode 2020–2023 menggunakan pendekatan Geographically and Temporally Weighted Regression (GTWR). Variabel yang dianalisis meliputi Rata-Rata Lama Sekolah (RLS), Produk Domestik Regional Bruto (PDRB), Tingkat Pengangguran Terbuka (TPT), Upah Minimum Kabupaten/Kota (UMK), dan Kepadatan Penduduk. Hasil menunjukkan model GTWR dengan kernel adaptive exponential memiliki kinerja terbaik (R² = 79,51%) dibanding OLS (R² = 61,4%). Rata-Rata Lama Sekolah (RLS) menjadi faktor paling dominan dalam menurunkan kemiskinan, baik secara tunggal maupun dalam kombinasi dengan PDRB.